PENGEMBANGAN DIARY BOOK OF SCIENCE BERSINTAK DISCOVERY BERPENDEKATAN STEM UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN KEMAMPUAN KOMUNIKASI ILMIAH PESERTA DIDIK - Meila Fride Fikriana; Wiyanto Wiyanto; Sri Haryani (Postgraduate, University of Mataram, 2023)
This study aimed to obtain the product, feasibility and effectiveness of Diary Book of Science media with the STEM Approach Discovery syntax to improve Students' Concept Understanding and Scientific Communication Skills. The research and development method used in this study refers to the method developed by Borg & Gall. Data collection was carried out using questionnaires and tests. Diary Book of Science with the STEM Approach Discovery syntax was validated by three validators, namely material experts, media experts and linguists’ experts, to determine the feasibility of the product itself. Students carry out further validation to find student responses and get suggestions for media development. Diary Book of Science with Discovery syntax with a STEM approach is intended to use Diary, which has a discovery learning syntax which is then combined with a Science, Technology, Engineering, and Mathematics (STEM) approach to the material of the earth's structure and its dynamics. With the study's results showing that it can improve the ability to understand concepts and scientific communication skills, the score of material experts is 89%, media experts are 85.67%, and language experts are 78.67%. The expert validation results for the Diary Book of Science with the Discovery syntax and STEM approach, material for the structure of the earth and its dynamics as a whole, has a percentage of 84.4%. This percentage is included in the very feasible criteria. Media Diary Book of Science with the Discovery syntax with the STEM approach is effectively used to analyze conceptual understanding and scientific communication skills with an increasing percentage of students who achieve learning mastery scores as indicated by differences in pretest and posttest scores